Magnetization AC losses of iron-based Ba-122 superconducting tapes. (June 2021) - Kováč, J.; Kapolka, M.; Kováč, P.; Kopera, L.; Pardo, E.; Zhu, Y.C.; Yao, C.; Wang, D.L.; Ma, Y.W.
Highlights: Magnetization AC losses in iron based superconducting composites were studied. Temperature was varied from 20 K to 42 K. External magnetic field of frequencies 72 Hz and 144 Hz up to 70 mT was applied. Parallel as well as perpendicular field orientation was examined. Effect of eddy currents in Ag sheath were observed. Abstract: Magnetization AC loss measurements of singe- and seven-core Ba122/Ag tapes have been done by calibration-free method in the range of temperature from 20 K to 42 K and field magnitudes up to 70 mT in RMS with two frequencies 72 Hz and 144 Hz. A strong effect of eddy current losses in highly conductive Ag sheath was observed for single-core sample, but negligible for seven-core tape with more resistive AgSn alloy outer sheath. For the estimation of eddy current loss component, pure Ag foil was measured in the same range of temperatures and used for analytical subtraction from the total losses of Ba122/Ag. In addition, loss measurement of singe-core sample with chemically etched away Ag sheath was also done. AC loss measurements in perpendicular as well as parallel field orientation have shown a strong effect of the filament size.